Evidence for the Absence of La Crosse Virus, Rift Valley Fever Virus, and Bunyamwera Virus in Korean Domestic Pigs - Chung, Hee-Chun; Nguyen, Van-Giap; Park, Bong-Kyun (International Journal of Negative Results, 2017)
A surveillance study reports no detection of targeted bunyaviruses in domestic pigs in Korea. Methods, sampling frame, and assay limits are described to contextualize interpretation and surveillance value.
Keywords: LACV; RVFV; and BUNV